(untitled) (The Pakistan Development Review, 2006)
The issue of poverty is as old as economic development. A significant quantitative research on poverty has been undertaken for many decades all over the world in general and in developing countries in particular. However the issue of urban poverty has not been addressed effectively. Nevertheless urban poverty has until recently, been low on the agenda of development policy not only in the developing world but also in Pakistan because of dominant perception of urban bias and the need to counter this with a focus on rural development policy. The analysis of urban poverty is as necessary as the overall level of poverty in the country. There are many causes and determinants of urban poverty1 but distribution and management of economic and social resources in poverty reduction cannot be ignored. It is internationally recognised that poverty reduction and governance both are interrelated. Bad governance has made poverty reduction efforts ineffective [Blaxall (2000), Eid (2000) and Gupta, et al. (1998)], while poverty reduction projects provide fertile ground for corruption.2 The consensus emerges from this line of thinking is that good governance is necessary and effective for poverty alleviation efforts.